Relative efficacy of seed priming with potassium nitrate and tap water in relation to germination, invigoration, growth, nitrate assimilation and yield of pigeonpea (Cajanus cajan L.) - Tiwari, T.N.; Kamal, Dipti; Singh, Rajiv K.; Prasad, S. Rajendra (Annals of Agricultural Research, 2014)
A Field experiment was conducted over two consecutive years (2009-10 and 2010-11) at the research farm of Directorate of Seed Research, Mau to study the effect of potassium nitrate and tap water on seed quality parameters, growth and yield of pigeonpea (Cajanus cajan L.). Six varieties of pigeonpea viz: ’NDA 1’, ’Bahar’, ’LRG 30’, ’UPAS 120’, ’TS 30’ and ’Pusa 2002-2’ were primed with three concentrations (0.30, 0.40 and 0.50 %) of KNO3 and tap water for 6 hours and one unprimed set was kept as control. Results based on two years data revealed that pigeonpea seeds primed with KNO3 and tap water significantly enhanced the seed germination, seedling length, seedling dry weight, vigour index I and II and finally test weight and grain yield over unprimed control in allthe varieties. Among KNO3 concentrations, 0.30% showed significantly higher values in above characters over rest of KNO3 concentrations including tap water. Deteriorations in seed quality parameters, growth and yield of pigeonpea varieties were noticed when the concentration of potassium nitrate exceeded beyond 0.30%. Pigeonpea varieties differed significantly in respect ofall characters studied. Economics of all the treatments including control was calculated on perhectare basis.